RESEARCHING HEALTH OF EMPLOYED POPULATION AS A SOCIO-ECONOMIC CATEGORY IN TERMS OF UKRAINE TRANSFORMATIONS - Zaiukov, I. V. (Visnyk of Vinnytsia Politechnical Institute, 2017)
There have been analyzed social, economic, medical and demographic factors of political influence on public health, including its workable part in terms of transformations of Ukraine. There has been proved that strategic priority of the state in social and economic terms is the restoration, strengthening and development of this key component of human capital, as − health. There has been proposed the concept within the framework of building a new system of public health — namely, building motivation of self-preservation the health of employed population that should be based on the «welcome» principle.